Water Quality Assessment and Hydrochemistry of Shallow Groundwater in Bhara Kahu area, Islamabad, Pakistan : Water Quality Assessment and Hydrochemistry of Shallow Groundwater in Bhara Kahu area, Islamabad, Pakistan - Anwar Qadir; Alwina Farooq; Tahseenullah Khan; Muhammad Zafar; Asif Javed (International Journal of Economic and Environmental Geology, 2017)
The groundwater quality of Bhara Kahu, Islamabad has been evaluated using water samples collected from 8 localities. The analysis has been performed to determine the drinking and irrigation groundwater quality. The standard procedures were adopted after the American Public Health Association (APHA) for sampling. The analysis revealed the concentration of the Ca, K, Mg, Na, NO3, HCO3, SO4, Cl, Total Dissolved Solids (TDS), hardness, turbidity, pH, alkalinity and Electrical Conductivity (EC). The World Health Organization (WHO) standards were used to compare with the results for the determination of the quality of groundwater. It is concluded that the groundwater in the Bhara Khau area is not polluted and may be used for drinking purpose. The geochemical evolution of groundwater describes it to be of Ca-HCO3 type showing a single aquifer having a younger groundwater. The suitability of the groundwater determined by the EC and the sodium hazard determines the groundwater to be safe. Keywords: Groundwater, physicochemical, Bhara Kahu, hydrochemical facies.